ANALISIS STRATEGI PEMBELAJARAN AKTIF DALAM PEMBELAJARAN AKIDAH AKHLAK - Maisari, Ayu; Safrizal, Safrizal; Fadli, M. (LPPM UM Metro, 2025)
This research analyzes active learning strategies in Akidah Akhlak learning. Active learning strategies are learning approaches that require active participation from students in the learning process. Active learning strategies are important to deepen the understanding and application of religious values in everyday life. The background of the research shows that the subject of Akidah Akhlak is very important to shape the morals and faith of students, but the implementation of learning is still often dominated by teachers and less interesting, so students become passive and unmotivated. The research method used is a qualitative research. The purpose of this study is to identify the form of active learning strategies, analyze their application in the Akidah Akhlak learning process in the classroom, and find out the supporting and inhibiting factors for the implementation of these strategies. This strategy can help students to be more active in understanding and mastering the subject matter, and can also develop critical thinking skills